Colistin Induces S. aureus Susceptibility to Bacitracin - Si, Wei; Wang, Liangliang; Usongo, Valentine; Zhao, Xin (Frontiers in Microbiology, 2018)
Bacitracin has been used in topical preparations with polymyxin B for bacterial infections. Colistin belongs to the polymyxin group of antibiotics and is effective against most Gram-negative bacilli. This study investigated whether colistin could affect the susceptibility of S. aureus to bacitracin. S. aureus isolates were first incubated with colistin and the susceptibility of S. aureus to bacitracin was increased. The interaction between colistin and bacitracin on S. aureus was then confirmed by the checkerboard assay and the time-kill kinetics. The Triton X-100-induced autolysis was significant increased after S. aureus was exposed to colistin. Exposure to colistin also led to a less positive charge on the cell surface and a significant leakage of Na+, Mg2, K+, Ca2+, Mn2+, Cu2+ and Zn2+. Finally, disruptions on the cell surface and an irregular morphology were observed when the bacteria were exposed to colistin and bacitracin. Bacitracin had a stronger antibacterial activity against S. aureus in the presence of colistin. This could be due to the fact that colistin damaged the bacterial membrane. This study suggests that combination of colistin with bacitracin has a potential for treating clinical S. aureus infections.